The macroalga Ulva rigida affords genome protection to Drosophila melanogaster via dietary supplementation - Marques, A.; Ferreira, J.; Abreu, H.; Pereira, R.; Rego, A.; Gaivão, I.; Pacheco, M. (Spanish Journal of Environmental Mutagenesis and Genomics, 2018)
Currently, marine macroalgae have been defended as functional food, due to their beneficial properties (e.g. anti-inflammatory, immunomodulatory and anti-tumour). In contrast, their genome’s protective potential is still poorly studied, albeit some evidences about their antioxidant, antigenotoxic and antimutagenic effects. The green alga Ulva rigida is an edible species, native in the Atlantic coast and easily grown in aquaculture, although it is underexplored regarding its biomedical/nutraceutical potential. Yet, some studies reported the antigenotoxicity of U. rigida and U. fasciata extracts and the antioxidant potential of U. lactuca extract, suggesting that species of Ulva genus may increase genome protection. Nevertheless, it must be pointed that those studies evaluated only the effects of algae extracts through in vitro trials, disclosing a gap of knowledge about in vivo effects of the whole algae ingestion on genome integrity maintenance. Hence, our goal was the search for beneficial effects of U. rigida, through an increased genome protection, aiming a functional characterization of healthy foods and human health promotion. For that, the antigenotoxic potential of U. rigida was assessed in Drosophila melanogaster following a dietary exposure, and against an exposure to streptonigrin (mutagenic agent). Thus, somatic mutation and recombination test (SMART) and comet assay were adopted, measuring somatic mutations/recombination events and DNA breaks, respectively. Two concentrations of U. rigida were tested and groups were distributed according to the following conditions: C (control); 2.5U/5.0U (2.5 or 5.0% of U. rigida supplementation); S (streptonigrin); 2.5U+S/5.0U+S (2.5 or 5.0% of U. rigida supplem. + streptonigrin). Regarding the antigenotoxic potential measured through SMART, both alga doses were beneficial against the streptonigrin-induced damage, though no differences were observed between them. In parallel, both levels of diet supplementation with U. rigida revealed their antigenotoxic ability only against DNA breaks induced by streptonigrin and, in this case, 5.0U revealed higher antigenotoxic potential than 2.5U. Overall, a diet supplemented with U. rigida showed to promote genome protection in D. melanogaster, particularly against damage induced by streptonigrin. These findings may contribute to the algaculture industry development, as well as the reinforcement of the idea of algae as functional food.